Breaking the Code : An Investigation on The Vocal Registers of Malaysia’s National Songstress Puan Sri Saloma - Nur Fardilla Nadia, Abu Bakar; Mohd Fairuz, Zamani (Penerbit Universiti Sains Malaysia, 2023)
Investigations on vocal registers have been a great subject of debate. Early vocal pedagogues and scholars like Bacilly (1668–1690) and Behnke (1836–1892) paved the way for the modern-day investigation to take place through the categorisation of vocal registers across various music genres such as classical, jazz, and popular. However, an investigation on the vocal registers of Puan Sri Saloma (1935–1983) as a popular music icon of Malaysia has yet to be done. This paper intends to examine Saloma’s vocal registers through vocal analysis of five selected songs using case study as its research design. These songs are transcribed using music notation software (Sibelius) and analytical diagrams using similar software are produced to show the use of chest, middle, and head registers in each song. The finding shows the usage of the said registers and a diagram of Saloma’s vocal range is then produced, proving that Saloma was an alto. This study does not intend to limit Saloma’s vocal capability, but rather to celebrate her vocal prowess and encourage other scholars to conduct further investigations concerning Saloma as Malaysia’s national songstress.